Pinoresinol and 3,4',5,7-tetrahydroxy-3'-methoxyflavanone from the fruits of Silybum marianum (L.) Gaertn - Diep, Trinh Thi; Kiem, Phan Van; Dong, Nguyen Thuong; Tung, Nguyen Huu; Bang, Bui Thi; Minh, Chau Van; Braca, Alessandra (Vietnam Journal of Chemistry, 2014)
From the fruits of Silybum marianum (L.) Gaertn. cultivated in the North of Vietnam, (±)2,6-bis(4′-hydroxy-3′-methoxy-phenyl)-3,7-dioxabicyclo[3.3.0]octane (pinoresinol) (1) and 3,4′,5,7-tetrahydroxy-3′-methoxyflavanone (2) were isolated. Their structures were elucidated by analyses of the NMR and mass spectra in comparison with the reported data. This is the first report of both 1 and 2 from Silybum species.